(untitled) (Journal of the Management Sciences, 2024)
The influence of social media technologies on the marketing of retail firms’ operations in Imo State cannot be under-estimated. Social media marketing is the process of gaining customers’ attention and traffic for a business, aimed at increased brand presence through the internet. Social media marketing enhances brand awareness in addition to customer retention and satisfaction. Social media enable marketers to interact with customers, businesses, friends, families and other groups. It is important in that it helps in search engine optimization and increases rankings of websites of different companies. It was in the view of the importance of social media that the study was carried out to examine the influence of social media technologies on the marketing of retail firms’ operations in Imo State. Two research questions were raised by the researchers to guide the study in line with two specific objectives. The questionnaire was the instrument used to collect data and administered to the respondents by the researchers with the aid of four research assistants. A population of one hundred (100) retail shop owners within Owerri Municipality was used for the study. The entire population was used since the population was small and manageable. The mean and standard deviation statistics were used for the analysis, while the t-test and ANOVA statistics were used to test the null hypotheses. It was found out among others that the social media technologies that were generally used by retail shop business operators in Imo State among others were: Google, whatsApp, imo, Linkedln, youtube, yahoo, Facebook, Reuters, BBM, and 2go. It was also found that the social media technologies were very effective and efficient, easily accessible and preferred platforms for retail marketing businesses. There was no significant difference in the mean responses of shop owners and customers in Imo State. The study recommended among others that workshops and seminars from time to time should be organized for private and public business organization operators to keep abreast with current trends on internet marketing through social media technologies.